Impact of Training on Livestock Technology Transfer for Rural Poor Farmers Livelihood Improvement in Bangladesh (SAARC Journal of Agriculture, 2021)
The study was conducted to evaluate the impact of training facilitated by Nuton Jibon Livelihood Improvement Project (NJLIP) under Social Development Foundation (SDF) for transfer livestock technologies and livelihood improvement for rural poor farmers in Bangladesh. A total of 650 farming households were selected by baseline survey during January 2018 to June 2018.The training and non-training beneficiaries were primary level educated and their family size (4.52) was little lower than the national average (4.9). Average age was 36.73 and 35.12 years for training and non-training farmers, respectively. The rate and amount of loan was found higher with respondent received training than without training. Adoption rate of technologies was higher than the level of idea on the concept of housing, feeding, breeding and marketing. The training beneficiaries improved knowledge and skill on feeding, management and health care of livestock and poultry. Training and demonstration are considered two strong tools for adoption and dissemination of livestock technology. Herd and flock size was increased by training beneficiaries than non-training beneficiaries. Beneficiaries having training on various IGAs have expanded their land and asset possession to a greater extent compared to non-training beneficiaries. Housing and sanitation condition of training beneficiaries were higher than non-training beneficiaries. Increased annual income of training and non-training households was 19.43% and 13.30% where income from different IGAs of livestock was 32.19% and 14.53%, respectively. Livestock were not extremely price sensitive but more sensitive on non-price factors logistic support like institutional support, quality of input and availability of input. Thus, training was treated as vital tools for transfer livestock technologies to influence the poor farmer’s livelihood improvement of training household than non-training household.SAARC J. Agric., 19(1): 223-235 (2021)